Logo Shape and Color as Drivers of Change in Brand Evaluation and Recognition - Torbarina, Matia; Grgurić Čop, Nina; Jelenc, Lara (Naše gospodarstvo/Our economy, 2021)
The purpose of the present study was to test whether logo shape and color affect emotional and cognitive response to a new logo. In the explorative part of the study, the effect of the amount of each of the additive primary color on logo perception was examined. Research was done on a sample of 190 students whose ratings were used as logo description measures. Two independent vari- ables used in the study were logo shape (abstract vs. concrete) and logo color (original color vs. greyscale). Results showed that greyscale logos and logos that are concrete were recognized more accurately while liking was not related to either independent variable. It was also observed that the amount of red color in logo is negatively (correlated/related), and blue and green color are positive- ly related to both logo recognition and logo liking. Practitioners are advised to note that factors affecting consumers’ cognition and emotion are different. Scientists can extend findings on the effect of amount of individual colors in a logo. This is one of the first works of research that examined the effect of logo color on brand recognition and has approached studying color in this way of averaging amount of each of the additive primary colors. External validity of the research is enhanced by testing the younger generation in their natural habitat of mobile phone environment.